Effectiveness Of Thematic Learning In Improving Elementary School Students' Learning Outcomes - Dea Mustika; Dian Krismawati; Dwi Kurnianda; Muhammad Aidil; Putri Adeliarahmatilla; Suci Ramadha Lena (Penerbit Hellow Pustaka, 2025)
His study aims to analyze the effectiveness of thematic learning in improving the academic achievement of elementary school (SD) students. Thematic learning, which integrates various subjects under a single theme, is expected to create a holistic and meaningful learning experience. Using a qualitative approach with a case study design, this research involves fourth-grade teachers, fourth-grade students, and the principal of SD Negeri 138 Pekanbaru as research subjects. Data were collected through in-depth interviews, participatory observations, and document analysis, and then analyzed inductively through the stages of data reduction, data presentation, and conclusion drawing/verification. The results of the study indicate that thematic learning is proven to be effective in increasing student motivation and engagement, facilitating a more holistic and in-depth understanding of concepts, and developing 21st-century skills (collaboration, communication, critical thinking). However, challenges in implementation—such as the availability of resources and the need for ongoing teacher training—were also identified.